Pedagogic Competency of Islamic Religious Education Teachers in Developing Educational Learning Activities in SMP Negeri 20 Medan - Haidir Haidir; Devi Umi Solehah; Khodijah Zuhro Annawawi Batubara; Khairul Ameer (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aims: (1) To determine how the instructional design of Islamic Religious Education teachers at SMP Negeri 20 Medan. (2) To find out how the implementation of Islamic Religious Education teacher teaching at SMP Negeri 20 Medan. (3) To find out what the teaching media for the Islamic Religious Education teacher at SMP Negeri 20 Medan. This research use desciptive qualitative approach. Data collection was carried out by observation, interviews, and documentation. Data analysis was carried out, namely examining all data, reducing data, presenting data, and concluding existing data.